2008
DOI: 10.1088/0022-3727/41/16/165101
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of transient electroluminescence in organic light emitting diodes

Abstract: Mathematical simulation on the rise and decay kinetics of transient electroluminescence (EL) in organic light emitting diodes (OLEDs) is presented. The transient EL is studied with respect to a step voltage pulse. While rising, for lower values of time, the EL intensity shows a quadratic dependence on (t − tdel), where tdel is the time delay observed in the onset of EL, and finally attains saturation at a sufficiently large time. When the applied voltage is switched off, the initial EL decay shows an exponenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…External quantum efficiency calculations were made as reported by Shukla et. Al [19] by the J-L-V and EL spectra. The angular dependence of the EL intensity and corresponding spectra were also measured with a home-made set-up including a motorized goniometer.…”
Section: Methodsmentioning
confidence: 99%
“…External quantum efficiency calculations were made as reported by Shukla et. Al [19] by the J-L-V and EL spectra. The angular dependence of the EL intensity and corresponding spectra were also measured with a home-made set-up including a motorized goniometer.…”
Section: Methodsmentioning
confidence: 99%
“…The transient electroluminescence (EL) measurement technology is widely used to investigate the carriers transport, accumulation and capture in organic thin films [6,7]. People have done a series of studies on the carriers transport process in OLEDs by using transient EL measurement technology, including the transient characteristics and the capacitance characteristics of OLEDs [8][9][10][11][12][13][14][15]. Our research group has studied the influence of the hole injection barrier, driving voltage and electron transport layer on carrier transport, and achieved some results.…”
Section: Introductionmentioning
confidence: 99%
“…For the advantages of low driving voltage, fast response, wide view angle, and flexible characteristics, organic light-emitting diodes (OLEDs) have attracted widespread interest and research. Response characteristics are important in fast display devices and infrared upconvertors. , In our previous investigation we reported that the transient electroluminescence (EL) was influenced by hole injection barrier, device structure, and light-emitting materials; e.g., the delay and decay time of transient EL were influenced by the insertion of MoO 3 . As a buffer layer, MoO 3 improved brightness and efficiency significantly by lowering the hole injection barrier.…”
Section: Introductionmentioning
confidence: 99%